Household debt, student loan forgiveness, and human capital investment: a neo-Kaleckian approach - Serra, Gustavo Pereira [UNESP] (Taylor & Francis, 2023)
This paper aims to analyze the sustainability of student debt in the US. For this purpose, I build a neo-Kaleckian model in which households can borrow to either consume or invest in human capital. Next, I calibrate the model using US data to simulate the economic effects of specific policies such as student loan forgiveness. To my knowledge, this is the first study that considers household borrowing for two different purposes, consumption and human capital accumulation, in a demand-led macro-modeling framework. The main findings are that (i) household debt is sustainable in the long run (i.e., the debt servicing is compatible with the long-term economic growth) for a consumption level greater than 90% of household income; (ii) new borrowing boosts short-term economic activity while having ambiguous long-term effects because of its outcomes to household indebtedness and debt servicing; and (iii) student loan cancelation has only short-run economic effects, whereas reducing loan interest rates and changing the eligibility criterion for student loan forgiveness result in long-term effects.
Keywords: Capacity utilization; household debt; human capital; post-keynesian economics; student loans